Nature or Nurture: Is the Digestive System of the Pontoporia blainvillei Influenced or Determined by Its Diet? - Tostado Marcos, Carlos; Olocco Diz, Julieta; Martín Ortí, Rosario; Loureiro, Juan Pablo; Molpeceres Diego, Ignacio; Tendillo Domínguez, Enrique; Pérez Lloret, Pilar; Santos Álvarez, Inmaculada; González Soriano, Juncal Milagros (Animals, 2024)
Author Contributions: Conceptualization, C.T.-M., R.M.-O. and J.G.-S.; methodology, C.T.-M., J.G.-S. and R.M.-O.; data collection and validation, C.T.-M., I.M.-D., J.-P.L. and E.T.-D.; formal analysis, I.S.-Á., R.M.-O., M.J.O.D. and J.G.-S.; resources, C.T.-M., M.J.O.D., I.M.-D. and J.-P.L.; writing— original draft preparation, C.T.-M., I.M.-D., M.J.O.D. and P.P.-L.; writing—review and editing, J.G.-S., R.M.-O. and I.S.-Á.; supervision, C.T.-M., R.M.-O., I.S.-Á. and J.G.-S.; project administration, J.-P.L., I.M.-D., C.T.-M., E.T.-D. and M.J.O.D.; funding acquisition, J.-P.L. All authors have read and agreed to the published version of the manuscript. The Franciscana (also known as the La Plata River Dolphin) is a small dolphin that lives in the coastal waters of Brazil, Uruguay, and Argentina. This species is considered the most endangered marine mammal in the western South Atlantic Ocean. Anatomic dissection of the digestive system of 19 animals of different ages, including 2 neonates, 12 juveniles, and 5 adults, was performed. Parameters related to length, breadth, weight, and diameter of the digestive viscera were considered in each case. Our results show that the Franciscana dolphin presents differential characteristics in relation to several parts of the digestive system, including, specifically, the tongue, the teeth, the stomach, and the small intestine. Thus, this paper add precious information to the actual knowledge of this vulnerable marine mammal species in order to improve conservation efforts. Depto. de Anatomía y Embriología Fac. de Veterinaria TRUE pub